Musical Memory - Turnšek Murko, Nika (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter presents various studies examining the impact of music on memory and learning. Anderson et al. (2000) investigated the use of background music to enhance students' spelling skills, finding that music helps students relax, focus on tasks, and improve their performance. Additionally, studies on musical memory have shown that musicians possess better verbal memory, as their musical training positively affects verbal recall (Ho et al., 2003). Borelle et al. (2014) studied the effect of music on working memory but found no significant impact of music on complex memory tasks, although music's influence on mood indirectly affects cognitive abilities. Finally, an exercise is presented that utilizes music to strengthen memory skills by helping students associate music with learning and information recall.